1928
DOI: 10.1021/ja01395a025
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Reactions Relating to Carbohydrates and Polysaccharides. Xv. The Isomeric Benzylidene Glycerols

Abstract: Fischer3 was the first to describe a definite condensation product from the interaction of glycerol with benzaldehyde and the molecular structure of the cyclic acetal formed was represented as being

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1928
1928
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Hill et al 6 showed that the 1,2-product is favored over the 1,3-product by a ratio of 5.7:1 in the absence of solvent. Data from Baggett et al 8 also favor the 1,2-product, but only by a ratio of 1.9:1.…”
Section: Process Conceptmentioning
confidence: 99%
“…Hill et al 6 showed that the 1,2-product is favored over the 1,3-product by a ratio of 5.7:1 in the absence of solvent. Data from Baggett et al 8 also favor the 1,2-product, but only by a ratio of 1.9:1.…”
Section: Process Conceptmentioning
confidence: 99%
“…A similar conformational preference of alkoxy groups (and other polar substituents) has been noted for substituents at C5 in the 1,3-dioxane ring system.15 Kaloustian16 has described the solvent dependence of this system by assuming that the conformational energy difference between two conformers can be represented by £ ± -struct T £soiv ± A£djp0¡e (5) and structbonds T angles T -Etorsional (6) -Estruct should be solvent independent, since the energy terms are those arising from intramolecular effects. However, £50 , the difference in solvation energies, and A£dipoie.…”
Section: Resultsmentioning
confidence: 75%
“…Acetal formation between substituted benzaldehydes and glycerol occurs widely in LSIMS/FAB mass spectrometry ( Table 1). An acetal peak is observed at the first scan, even though organic synthesis of acetal from benzaldehyde and glycerol (H 2S04 catalyst) needs an 8-h heating at 100°C to obtain a yield of 39% [25]. Rapid condensation is therefore believed to be beam induced in the mass spectrometer source.…”
Section: Resultsmentioning
confidence: 99%
“…As previously mentioned, acetal formation between benzaldehydes and glycerol (acid catalyst) is also encountered in organic synthesis. In such a case, the product obtained is a mixture of five-and sixmembered cyclic benzylideneglycerol acetals [25,26] in which the five-membered cyclic acetal (2) predominates. With a catalytic amount of acid, a slow equilibrium is established between these two isomers with in the 0.114-0.119 range [27].…”
Section: Structure Of the {Solute + Glycerol + H -H10]+ Clustermentioning
confidence: 99%